It seems that some the work is already here, but I'd be glad to!! So for #3 which is 9x^2+15x, we can factor out both a 3 and an x (3x) so we know that 3x * 3x =9x^2 and 3x * 5 = 15x so once we take the 3x out of the equation, we are left with 3x(3x+5) and that's as far as you can factor.
For #4, we see that the common factor is 10m because 10m * 2n = 20mn and 10m * 3 = 30m so once we take 10m out of the original, it becomes 10m(2n-3)
For #5, this one the common factor is 4xy because 4xy * 2xy=8x^2y^2 and 4xy*x= 4x^2y and 4xy*3=12xy so once we take the 4xy out of the equation, it becomes 4xy(2xy-x-3)
Hope this helps!
Answer:
11 1/2 aka D
Step-by-step explanation:
add 7 and 4 which is 11, then add 1/4 and 1/4 which is 1/2
Answer: #20, x = 3
#21, x = 1/2
Step-by-step explanation:
#20) x + 4 + x + 2+ x + 5 = x + 3 +x+3+x+1+x+1
3x + 11 = 4x + 8
<u>-3x -3x</u>
11= x + 8
<u> - 8 - 8</u>
3 = x
#21) 12x(5) = 6x + 9 + x + 10 + x + 7
60x =8x + 26
<u> -8x -8x</u>
52x = 26
divide both sides by 52
x = 1/2
Answer:
F(x) and h(x)
Step-by-step explanation:
f(x) has a high of three and so does H(x), g(x) has a high of -2 so it doesn't count